Postern of fate [large type] : a Tommy and Tuppence mystery - Christie, Agatha, 1890-1976 (A Tommy and Tuppence mystery, 2014)
"When the Beresfords obtain an old house and its contents, Tuppence discovers a series of underlinings in a copy of The Black Arrow. When she writes down the letters, they spell out a very disturbing message: "Mary Jordan did not die naturally." After sixty years, Mary Jordan's enemies are still ready to kill"--